Effects of strenuous exercise on baseline ventricular function and inotropic, chronotropic and lusitropic response in mice - Wilensky, Luciana (2013)
Background: Mild to moderate exercise reduces cardiovascular risk factors, improves pre-existing pathological conditions and develops adaptive cardiac hypertrophy. However, the myocardial response to strenuous exercise is scarcely known. Objective: The aim of this study was to evaluate baseline ventricular function and myocardial reserve (inotropic, chronotropic and lusitropic response to the β-adrenergic agonist isoproterenol) in vivo and in vitro in mice following strenuous exercise. Methods: Three-month old male FVB mice were used. The protocol exercise consisted in 90 min swimming sessions twice a day, 6 days/week for 4 weeks. Two experimental groups were studied: 1) sedentary group, with no exercise; and 2) exercise group, with full strenuous swimming protocol. Results: At the end of the protocol, left ventricular mass increased by 27.9±4% with preserved baseline left ventricular function. In vivo and in vitro myocardial response to isoproterenol decreased with no changes in interstitial collagen. Conclusions: Under our experimental conditions, a strenuous swimming protocol produced moderate cardiac hypertrophy with adaptive and maladaptive hypertrophic characteristics. Although baseline ventricular function was preserved with no changes in interstitial collagen, inotropic, chronotropic and lusitropic reserve decreased.